Respuesta:
x2 - 4x + 4 = 0
[tex]x = \frac{ - (b \: ± \: \sqrt{ {b}^{2} - 4ac} }{2a} [/tex]
a = 1
b= -4
c= 4
[tex]x = \frac{ - ( - 4)± \sqrt{ {( - 4)}^{2} - 4. \: 1. \: 4} }{2.1} [/tex]
[tex]x = \frac{4 \: ± \: \sqrt{16 \: - 4 \: .1 \: .4 \: } }{2.1} [/tex]
[tex]x = \frac{4 \: ± \: \sqrt{16 - 16} }{2.1} [/tex]
[tex]x = \frac{4 \: ±\sqrt{0} }{2.1} [/tex]
[tex]x = \frac{4 \: ± \: 0}{2.1} [/tex]
[tex]x = \frac{ \: 4 \: }{ \: 2.1 \: } [/tex]
[tex]x = \frac{4}{2} [/tex]
[tex]x = 2[/tex]
Explicación paso a paso:
Saludos desde USA